Dekonstruksi Fungsi Kontrol dan Eksistensi Lembaga Adat Upu Hena dalam Harmonisasi Masyarakat Negeri Amahai Kabupaten Maluku Tengah - Tanamal, Johan; Soselisa, Hendry Ch; Louhatu, Djayanti (KOMUNITAS: Jurnal Ilmu Sosiologi, 2025)
This study examines the weakening role and existence of the Upu Hena Customary Institution in Tanah Amahai, Central Maluku Regency. Traditionally, customary institutions played a central role in establishing norms, resolving conflicts, and maintaining social harmony. However, modernization and shifts in community mindsets have reduced the legitimacy of customary law as a mechanism of social control. Issues such as juvenile delinquency, fights, and violations of customary norms reflect this decline, while communities increasingly prefer to resolve disputes through state authorities. The research aims to deconstruct the function of social control and the presence of Upu Hena in sustaining community harmony. Using a qualitative method with an ethnographic approach, the study analyzes data through three theoretical frameworks: Derrida’s social deconstruction, Parsons’ structural functionalism, and Berger & Luckmann’s social construction. Findings reveal that adat represents a realm of meaning continuously reinterpreted to remain relevant to changing times. Beyond preserving traditions, the institution enforces sanctions, strengthens solidarity, and transmits cultural values through deliberation and practice, ensuring its role as both a mechanism of social control and a guardian of collective identity.